Spatial Socialization and School. Theory and Practice of a Building Block for Teacher Education in Human Geography - Schlottmann, Antje; Mösgen, Andrea; Böhm, Thomas (Journal of Geography Education, 2014)
School is an integral part of the quarter it is located in. At the same time, and given a growing number of all-day schools in particular, it is an important part of the life worlds and identities of its pupils. Against the background of a resulting responsibility for teachers to address and deal with the spatial conditions of their educational practice, this paper discusses the advantage of empirical research into social spaces as a part of higher education for teachers in Human Geography. First, we lay out the scholarly field of the analysis of quarters by identifying different approaches. We consider a focus on life worlds and practices of spatial appropriation to be most productive. In a second part, the geographical and epistemological competences that can be enhanced are addressed in detail. In a third section we present a one-year teaching module for teacher education that we have designed and implemented at Frankfurt University in order to meet the identified requirements of human geographic literacy. The paper concludes with some reflections on the challenges and possible pitfalls of such an undertaking in teaching. We point out three main didactical suggestions that might help to tap the full potential of teaching teachers social area analysis.